Awareness about Common Disinfection Procedures among Undergraduate Students in Clinics - S.Santhosh Bala1 , N.P Muralidharan2 , Vivek Narayan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dentists, dental patients and dental technicians are tasked with various dental procedures which are extremelyprone to cross contamination of various infections from various pathogens usually found in blood and dentaloffices. A lot of attention has been directed towards proper medical care, sterilization and instrument care.Online survey containing the questionnaire was sent to 100 undergraduate dental students. Results weretabulated and analysed. The questionnaire was based on the knowledge they gained during their studentdays. Among them 53% are aware of general principles of disinfection , 85% level of disinfection determinesquality of clinical practice. Within the limits of the study , the awareness about common disinfectionprocedures among undergraduate dental students in clinics was evaluated . Upon evaluation it was found thatthe student dentist had a moderate level of knowledge about disinfection in clinics, which can be improvedby extensive teaching about disinfection practices and improving knowledge.